Taxonomic revision of the speckled crabs, genus Arenaeus Dana, 1851 (Brachyura: Portunidae) based on morphological and molecular data - Zupolini, Lucas L.; Magalhães, Tatiana; Pileggi, Leonardo G.; Mantelatto, Fernando L. (Zootaxa, 2017)
The family Portunidae Rafinesque, 1815 presents a series of taxonomic problems such as paraphyletic groups, synonymizations, and unresolved complexes of cryptic species. Arenaeus Dana, 1851, encompasses only two species with mirrored distributions along the coasts of the Americas. Despite of comprising two widespread species, there is a scarcity of information on their biology and ecology and on the relationships with other genera in the family. Because of the lack of studies comprising both species and the imprecise or erroneous taxonomic descriptions for the species of Arenaeus, we conducted a thorough taxonomic revision of the genus and used data from fragments of the 16S rRNA and the cytochrome oxidase I (COI) genes to investigate the validity of Arenaeus cribrarius (Lamarck, 1818) and Arenaeus mexicanus                 (Gerstaecker, 1856). A range of easily discernible and objective characteristics distinguish the species, including the number of rostral teeth, the number of carpal spines, and the presence of a spine on the epistome region. This last feature, although never properly addressed in the literature, was diagnostic in discriminating the taxa. Results of molecular analyses also supported the separate identity of the two species. Assemblages generated in COI analyses reflected no geographic pattern or geographic partitioning, suggesting that dispersion and gene flow could be sufficiently high to hinder genetic differentiation through the extensive distribution range of the Atlantic species, A. cribrarius. Furthermore, molecular results and morphological analyses may indicate a closer relationship among particular groups of portunids and Arenaeus. Morphology of the carapace and of the first male gonopods may be the most prominent characteristics supporting such view. We have shed light on the status of the genus Arenaeus and its members, clarified some taxonomical issues, and provide an identification key for the species.